Physical and chemical processes in the application of antifriction coatings by the friction-mechanical method - A.M. Krasota; I.V. Shepelenko; M.V. Krasota (Проблеми трибології, 2025)
The current models of antifriction coating formation by finishing antifriction non-abrasive treatment has shown the lack of a thorough analysis of physical and chemical processes occurring in the friction zone. From this point of view, it seems reasonable to study the process of coating formation at the stages of surface activation, deposition of antifriction components and formation of an antifriction coating. The considered characteristic structures for each of the stages of antifriction coating application and chemical reactions that occur during the formation of an antifriction coating allow us to track the processes accompanying the formation of coatings and identify ways to improve them. It is proved that the quality of coating formation directly depends on the material of the part and tool, temperature in the deposition zone, material diffusion rate, and dissociation of chemical compounds. A physical model of the process of finishing antifriction  treatment is proposed, which determines the chemical reactions and physical processes occurring at different stages of the coating formation. The analysis of the model allows to find out  the characteristic phenomena in the system ‘part – tool – technological environment’, and to influence the quality of the formation of an antifriction coating by the friction-mechanical method.